STEM-H for mental health clinicians - Weaver Lewis, Marilyn; Wu, Liyun; Hagen, Zachary Allan (Oxford University Press, 2023)
STEM-H for Mental Health Clinicians introduces a new model that adapts scientific, technological, engineering, and mathematical concepts to treat the health (STEM-H) of patients with medical problems. The book begins with a discussion of genetics and continues through current scientific research underlying each bodily system to inform practitioners and advanced students about development, as well as structure, and function. Signature illnesses and injuries that affect each system are discussed at length, as well as technological advances and biomedical engineering that developed apparatuses and medications to treat those signature conditions. Mathematical concepts that underlie public health models are introduced in each chapter and range from the prevalence and incidence of these medical conditions to social determinants of health, and the relationship of ethnicity, gender, and poverty. Clinical theories and methods are introduced to inform practitioners about treatments of signature illnesses and injuries experienced by children and adults. The book thoroughly explains the terminology and STEM-H concepts to inform students and mental health clinicians. Readers who master the material will be prepared to work as medical team members or as independent clinicians with private or community clients who struggle with medical problems. This textbook addresses the well-being of the patient's family members and introduces solutions to improve the caregivers' burden. Chapters in STEM-H for Clinicians provide a bench-side to bedside approach to apply basic global scientific data, predominantly from the United States, that inform clinicians' treatment methods and develop research-informed practice